Simplification of culture conditions and feeder-free expansion of bovine embryonic stem cells - Soto, Delia Alba (2021)
Bovine embryonic stem cells (bESCs) extend the lifespan of the transient pluripotent bovine inner cell mass in vitro. After years of research, derivation of stable bESCs was only recently reported. Although successful, bESC culture relies on complex culture conditions that require a custom-made base medium and mouse embryonic fibroblasts (MEF) feeders, limiting the widespread use of bESCs. We report here simplified bESC culture conditions based on replacing custom base medium with a commercially available alternative and eliminating the need for MEF feeders by using a chemically-defined substrate. bESC lines were cultured and derived using a base medium consisting of N2B27 supplements and 1% BSA (NBFR-bESCs). Newly derived bESC lines were easy to establish, simple to propagate and stable after long-term culture. These cells expressed pluripotency markers and actively proliferated for more than 35 passages while maintaining normal karyotype and the ability to differentiate into derivatives of all three germ lineages in embryoid bodies and teratomas. In addition, NBFR-bESCs grew for multiple passages in a feeder-free culture system based on vitronectin and Activin A medium supplementation while maintaining pluripotency. Simplified conditions will facilitate the use of bESCs for gene editing applications and pluripotency and lineage commitment studies.